Konsistensi ruang pangimaman, liwan, dan pawestren di Masjid Pathok Negara Ad-Darojat Babadan, Bantul, Yogyakarta (1970-2019) - Denny Huldiansyah; Tarcicius Yoyok Wahyu Subroto (ARTEKS : Jurnal Teknik Arsitektur, 2020)
The consistency of pangimaman, liwan, and pawestren in Masjid Pathok Negara Babadan, Bantul, Yogyakarta (1970-2019) Masjid Pathok Negara Babadan is one of four Pathok Negara Mosques which act as the eastern border of the state in the era of Sultanate of Yogyakarta. The Mosque has gone through many physical alterations especially within its current spaces. However, behind these alterations there are spaces whose existence have been consistent since the mosque was established until now. This raises questions such as what are the consistent spaces in Masjid Pathok Negara Babadan and what affects the consistency of those spaces. This study uses qualitative-descriptive method in order to collect data and informations about the development of floorplans and spaces in Masjid Pathok Negara Babadan. The analysis is conducted by using diachronic method and Cartesian Coordinat System (CCS). The findings of the study reveal that the existence of pangimaman, liwan, and pawestren are consistent space in Masjid Pathok Negara Babadan. This consistency is affected by the palace’s authority as the owner of sultanate’s mosques (kagungan dalem), including Masjid Pathok Negara Babadan itself. © 2020 Denny Huldiansyah, Tarcicius Yoyok Wahyu Subroto